HUBUNGAN PERANAN KEPEMIMPINAN DENGAN DISIPLIN KERJA TENAGA KESEHATAN DI UPT PUSKESMAS PADANG BULAN TAHUN 2019 - Pinta Alfiani Telaumbanua; Rapael Ginting (Fakultas Kesehatan Masyarakat Institut Kesehatan Medistra Lubuk Pakam, 2019)
Discipline is a matter that becomes a benchmark to find out whether the overall role of the leader can be carried out properly or not. Discipline must be upheld in an organization, without the support of the discipline of health workers it is difficult to realize its goals, so discipline is the key to the success of an organization in achieving its goals. This type of research uses analytic survey method with cross sectional design, to explain the relationship between the role of leadership and work discipline at UPT Puskesmas Padang Bulan. With a total of 48 respondents, the total sampling technique is to make the entire population into the study sample. The results of bivariate analysis using the Chi-Square Test obtained p value = 0.004 (p value <0.05), meaning Ha was accepted and Ho was rejected, which means there was a significant relationship between communication with the workforce health discipline at the Padang Bulan Health Center UPT 2019. The results of bivariate analysis using the Chi-Square Test obtained p value = 0.001 (p value <0.05), meaning that Ha is accepted and Ho is rejected, which means there is a significant relationship between Direction and Guidance with the discipline of health workforce at UPT Padang Bulan Health Center in 2019. It is hoped that leaders will improve communication, direction and guidance for health workers to create a condition of good work discipline.